2012
DOI: 10.1085/jgp.201210779
|View full text |Cite
|
Sign up to set email alerts
|

Local anesthetic inhibition of a bacterial sodium channel

Abstract: Recent structural breakthroughs with the voltage-gated sodium channel from Arcobacter butzleri suggest that such bacterial channels may provide a structural platform to advance the understanding of eukaryotic sodium channel gating and pharmacology. We therefore set out to determine whether compounds known to interact with eukaryotic NaVs could also inhibit the bacterial channel from Bacillus halodurans and NaChBac and whether they did so through similar mechanisms as in their eukaryotic homologues. The data sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
93
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(103 citation statements)
references
References 27 publications
9
93
1
Order By: Relevance
“…The discovery of the bacterial ion channel family Na v Bac (4,5), and subsequent solution of high-resolution structures (6,7), has given us an opportunity to begin to understand Na v function at the molecular level. The homotetrameric Na v Bac structures are far simpler to study structurally and functionally and are modulated by drugs in similar ways to their mammalian counterparts (8), making them ideal systems to explore the molecular mechanisms of Na v function.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of the bacterial ion channel family Na v Bac (4,5), and subsequent solution of high-resolution structures (6,7), has given us an opportunity to begin to understand Na v function at the molecular level. The homotetrameric Na v Bac structures are far simpler to study structurally and functionally and are modulated by drugs in similar ways to their mammalian counterparts (8), making them ideal systems to explore the molecular mechanisms of Na v function.…”
mentioning
confidence: 99%
“…Inactivation is associated with numerous neuronal and cardiac pathologies (26). Bacterial channels display slow inactivation reminiscent of C-type inactivation in K v channels (27), involving its PD (28,29), and is known to be modulated by local anesthetics (8). Interestingly, there is recent evidence that mammalian channels are also affected by this process (30)(31)(32), despite a historical focus on fast inactivation (33).…”
mentioning
confidence: 99%
“…Mutations in human sodium channels (hNa v s) have been linked to channelopathies such as epilepsy, cardiac arrhythmia, and chronic pain syndromes; consequently sodium channel blockers have been developed as anticonvulsant, antiarrhythmic, and local anesthetic drugs (7)(8)(9)(10). Several eukaryotic calcium channel blocker drugs have previously been found to bind and block prokaryotic sodium channels (11)(12)(13).…”
mentioning
confidence: 99%
“…These anesthetic agents reduce peak current and accelerate current decay, making it conceivable that local and general anesthetic agents could share a site of action in NaChBac. The local anesthetic binding site identified in the central cavity of the mammalian Na V 1.2 channel, which mediates open channel block, is partially conserved in NaChBac (37,38). A recent molecular dynamics (MD) modeling study found that isoflurane, which inhibits NaChBac (15), interacts with multiple regions of this channel, including the pore, the selectivity filter, and the S4-S5 linker/S6 interface (39).…”
mentioning
confidence: 99%
“…Additionally NaChBac exhibits conserved slow open channel block in response to local and general anesthetic agents (15,37). These anesthetic agents reduce peak current and accelerate current decay, making it conceivable that local and general anesthetic agents could share a site of action in NaChBac.…”
mentioning
confidence: 99%